PHYSICAL, MICROSTRUCTURAL AND SENSORY CHARACTERISTICS OF EXTRUDED AND MICROWAVE-EXPANDED SNACKS ADDED WITH DEHYDRATED SQUASH - Delgado-Nieblas, C. I.; Zazueta-Morales, J. J.; Aguilar-Palazuelos, E.; Jacobo-Valenzuela, N.; Aguirre-Tostado, F. S.; Carrillo-Lopez, A.; Ruiz-Armenta, X. A.; Telis-Romero, J. [UNESP] (Univ Autonoma Metropolitana-iztapalapa, 2018)
The objective of this work was to study the effects of the extrusion temperature (T, 93-141 degrees C), feed moisture content (FMC, 21.27-34.73%), and dehydrated squash content (DS, 0.43-15.57%) on physical, microstructural and sensory characteristics of microwave-expanded snack foods (SF) formulated adding dehydrated squash to a base blend of corn starch-yellow corn. A second order rotatable central composite design and the response surface methodology for data analysis were used. The T and FMC showed a greater effect (P < 0.05) on specific volume and moisture of pellets, whereas FMC and DS showed a greater effect on Chroma (C*) and Hue (H*) color parameters. The microstructural properties of the snacks evaluated with the Rapid Visco-Analyzer (RVA), Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) were related mainly to the starch gelatinization. Also, the sensory acceptability of snacks added with DS reached almost 79%. The results indicate that it is possible to elaborate SF with acceptable physical and sensory characteristics by adding DS to a base blend.
Keywords: dehydrated squash; extrusion; microstructural properties; sensory acceptability; snacks